Microstructure-sensitive accumulation of plastic strain due to ratcheting in bearing steels subject to Rolling Contact Fatigue - Pandkar, Anup S.; Arakere, Nagaraj; Subhash, Ghatu (International journal of fatigue, 2014)
•Localized ratcheting during RCF is studied at the microstructural scale.•The origin of ratcheting near heterogeneous carbide particle is also investigated.•During RCF, carbides alter the shear stress cycle, promoting localized ratcheting.•A novel method for estimating cyclic hardening parameters is presented.•The results presented are also applicable to other heterogeneous materials. It is well known that the empirical parameters correlated to Rolling Contact Fatigue (RCF) bench tests are sensitive to the microstructural attributes of the bearing material. The key driver for this sensitivity is the accumulated deformation accentuated by the difference in the mechanical properties of the carbide precipitate, matrix, and interface. This manuscript studies the accumulation of deformation/micro-plastic strain during RCF due to ratcheting behavior in the microstructure of bearing steels. The objective of this study is to understand the contribution of carbide particles towards ratcheting. Homogeneous elastic–plastic finite element (FE) simulations of the ball-on-rod RCF test using a ‘global–local’ approach is used, and is applicable when the drivers for fatigue degradation are controlled primarily by the heterogeneous field represented by the carbides. The global model simulates the overall ball-on-rod RCF test considering homogeneous material, while the local model accounts for the influence of the carbide particles in the microstructure. The results from finite element simulations reveal that carbide particles act as stress concentrators and introduce a shear stress cycle with a non-zero mean stress at the scale of the carbide microstructure, which promotes strain accumulation via ratcheting. A study on the spatial variation of ratcheting behavior in the vicinity of the carbide particle is also presented. The results presented translate to other through and case-hardened bearing steels subject to RCF and highlight the important role played by the carbide microstructure in controlling the spatial and temporal rate of fatigue damage accumulation via localized ratcheting. The approach presented has general applicability to heterogeneous materials with other forms of heterogeneity such as inclusions, pores and grain boundaries, subject to multiaxial fatigue.